PERAN NORMA DAN SOLIDARITAS DALAM KOLABORASI POLSEK DAN MASYARAKAT STRATEGI ADVOKASI, MEDIASI, NEGOSIASI UNTUK MENEKAN KRIMINALITAS DI UNGARAN BARAT - Callista Aurora Suarez; Alvianto Wahyudi Utomo; Rizky Amalia Yanuartha (Laborataorium Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2026)
This study addresses the persistent problem of crime in communities, which necessitates a comprehensive approach that is not only legal and repressive but also social and participatory. The main objective of this research is to detail the forms of collaboration between the police (Polsek) and the community, explain the factors that contribute to its success, and identify the obstacles encountered during its implementation. Using a descriptive qualitative approach, this research delves into the collaborative efforts between the police and the community to reduce crime in West Ungaran District. Data was collected through in-depth interviews, participatory observation, and documentation in Sendangputri and Nyatnyono villages. The key findings show that the collaboration between the Polsek and the community, particularly in these two villages, has been effective through participatory and community-based approaches. Strategies such as advocacy, mediation, and negotiation have not only contributed to a significant reduction in crime rates but have also strengthened local social structures by increasing trust, citizen solidarity, and informal social control. The research concludes that this collaboration effectively reduces crime and enhances local social structures by using advocacy, mediation, and negotiation strategies.